Continuous assessment of the adaptability between river network connectivity and water security in a typical highly urbanized area in eastern China - Gu, Yicheng; Wang, Siru; Hu, Qingfang; Sun, Jinhua; Cai, Mei; Lu, Zhihua; Gao, Mingyuan (Frontiers in Environmental Science, 2022)
Urbanization has reduced river network connectivity, posing a great threat on water security. However, the mechanism through which changes in river network connectivity impact on water security remains uncertain. River network connectivity and water security have been separately and thoroughly assessed by several researchers; however, few studies conducted a coupled assessment of these two aspects together, which may shed light on this mechanism. Based on assessment indicators developed in previous studies and key influence factors identified in the study area, this study proposed a comprehensive evaluation method to continually evaluate the adaptability between river network connectivity and water security in Wuchengxiyu region, a highly urbanized area in eastern China. The continuous evaluation was conducted for the period 2010-2019 based on the coupling coordination degree calculation formula. The results show that from 2010 to 2015, the coupling coordination degree between river network connectivity and water security followed a downward trend, due to the uncoordinated development between water systems and urbanization. After 2015, an increasing trend was observed with the implementation of environmental policies. In the past decade, the water surface rate and the coverage rate of suitable flow velocity decreased from 4.59% to 4.28% and from 54.1% to 30.9%, respectively, which may have negative effects on water quality and limit the improvement of regional flood control capacity. Moreover, the evaluation results also prove that policies such as the Ecological River-lake Construction and the River Chief System have contributed to improve the quality of the water environment and regional flood control. The proposed assessment framework can be used as a guidance to evaluate the relationship between water network connectivity and water security; moreover, it provides new ideas for water network system protection and water quality maintenance in similar highly-urbanized areas.